Development of a screening tool for the need of specialist palliative care in oncologic inpatients: study protocol for the ScreeningPALL Study. Issue 9 (1st September 2022) - Müller, Evelyn; Müller, Michael Josef; Boehlke, Christopher; Ramsenthaler, Christina; Jäger, Helga; Schäfer, Henning; Ostgathe, Christoph; Klein, Carsten; Simon, Steffen; Becker, Gerhild
Abstract : Introduction: A range of referral criteria and scores have been developed in recent years to help with screening for the need of specialist palliative care (SPC) in advanced, incurable cancer patients. However, referral criteria have not yet been widely implemented in oncology, as they usually need to be revised by physicians or nurses with limited time resources. To develop an easily applicable screening for the need for SPC in incurable cancer inpatients, we aim to (a) test inter-rater reliability of multiprofessional expert opinion as reference standard for SPC need (phase I) and (b) explore the diagnostic validity of selected patient-reported outcome measures (PROMs) and routine data for the need of SPC (phase II). Methods and analysis: Inclusion criteria for patients are metastatic or locally advanced, incurable cancer, ≥18 years of age and informed consent by patient or proxy. (Exclusion criteria: malignant haematological disease as main diagnosis). In phase I, three palliative care consultation teams (PCTs) of three German university hospitals assess the SPC need of 20 patient cases. Fleiss' Kappa will be calculated for inter-rater reliability. In phase II, 208 patients are consecutively recruited in four inpatient oncology wards of Freiburg University Hospital. The PCT will provide assessment of SPC need. As potential referral criteria, patients complete PROMs and a selection of routine data on person, disease and treatment is documented. Logistic regression models and ROC analyses are employed to test their utility in screening for SPC need. Ethics and dissemination: Our findings will be published in peer-reviewed journals and presented at national and international scientific meetings and congresses. Ethical approval was granted by the Ethics Committee of Albert-Ludwigs—University Freiburg, Germany (approval no. 20-1103). Trial registration number: German Clinical Trials Register, DRKS00021686, registered on 17 December 2020.